Retorno ao trabalho após o nascimento de um filho: percepções de professoras sobre sua experiência. - Gravena, Ana Carolina (Universidade Federal de São Carlos, 2006)
The participation of women in the paid workforce has increased significantly in recent decades, allowing women to make an important contribution to the family income. Apart from their professional activities, many women are also responsible for the greater part of household labor and childcare activities. Reconciling these responsibilities can be difficult, due to the sheer number of activities to be accomplished, especially during periods when professional and family demands are intense. As such, returning to work following a maternity leave may be an especially difficult time, when the high volume of care for the baby is added to work routines. In addition, legislation that secures the right to a maternity leave does not guarantee adequate workplace support for mothers of infants and very young children. As such, mothers who return to work when their children are very young may experience difficulties to maintain a satisfactory involvement with their child, as well as maintaining their job performance. The extent to which the mother-child relationship is undermined is of great importance, given that poor maternal involvement is a risk factor for the development of later problems in early childhood, as this may have a negative effect on the emotional bonds between mother and child and reduce the frequency of stimulating interactions. This study identified sources of support and strategies used by teachers to reconcile childcare and paid work; the reactions and difficulties experienced by these mothers; their wellbeing; and the activities undertaken by them and by their husbands, in caring for their infants. Individual interviews were conducted, using questions with openended and fixed-format responses, including a series of scales to measure workplace factors and personal well-being, with 40 teachers who had children under two years of age. The results indicate that few strategies were used by the employers to support these women; their principal sources of support, although unsatisfactory, were their husbands and other close family members. In general, the study participants felt over burdened, with little time for themselves or to be with their children. Thus, one can see the importance of changes in the work environment and of a more equal division of household labor between the marital partners, representing initiatives that could generate positive changes in the women s professional and family experiences. Becoming a mother is treated as a private event that should not create an onus for the employer. However, the experiences of these women show the importance of having employers assume a more supportive posture, to guarantee the effective performance of their employees as well as their greater wellbeing during a period that is so critical in the life of these mothers, their children and the students they teach.
Keywords: Educação especial; Prevenção de deficiências; Licença maternidade; Professoras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL